Promoting the conservation and use of plant genetic resources by training and research: capabilities and capacities for plant genetic resources training in public universities and institutions in Eastern Africa - Tigerstedt, P.M.A.; Akundabweni, L.S.; International Plant Genetic Resources Institute (2002)
In the mid 1990s, it was realized that the plant genetic resources training approach through the provision of fellowships, and sponsoring of national and regional thematic training courses by IPGRI and other partners was not sustainable. This acknowledgement stimulated the need to search for an alternative and more sustainable approach. The involvement of local institutions spearheaded by the universities was identified as more appropriate. The involvement of the universities clearly fits into IPGRI's global training and capacity building efforts. It provides a window to sustainability and involvement of all the relevant national institutions in contributing to plant genetic resources training activities at the national and regional levels. This report is the result of visits made in the year 2000 to designated universities, institutes and organizations in Ethiopia, Kenya and Uganda to carry out a survey and gather such information. The document details information on capabilities relevant to PGR training within and among institutions. It particularly pays attention to the institutional capabilities; institutional capacities; and the model (institutional) links that are basic for setting up a consortium of stakeholders, not as individual persons but as communities of educators with a common vision and mission. The proposition for a consortium is an excellent one as it calls on country partners to participate by the comparative advantages each of their institutions possess. The ownership of the EAPGRTC is thus made participatory rather than centre-managed.The document finally recommends levels of training that can immediately be offered in an EAPGRTC context. It also identifies gaps observed on the ground and suggests ways to address them. The report further deliberates on the way forward as well as setting priorities for strengthening such a consortium so as to meet future PGR training and research needs in the East African region. The document should be useful in crystallizing a consortium initiative.